Performance and impacts of managed aquifer recharge interventions for agricultural water security: A framework for evaluation - Prathapar, Sanmugam A.; Dhar, S.; Rao, G.T.; Maheshwari, B. (Elsevier, 2015)
To minimize and counter decline of groundwater levels and improve the availability of water for cropproduction, Managed Aquifer Recharge (MAR) interventions are widely adopted across India, often ini-tiated or supported by, local communities, state and central governments to improve the availability ofwater for irrigation. While the literature on MAR in India is vast, the science of their construction is lack-ing. Furthermore, there is an absence of a structured approach to evaluate the performance and impactof MAR interventions. Often, performance and impacts of MAR have been commented upon together,without distinguishing the two.In this article, we aim to propose that performance and impact are different from each other, andthat the evaluation of MAR interventions should take into account such differences between them. Aframework for performance and impact analysis, based on three levels, viz. primary, secondary and ter-tiary, is outlined. It is then applied to seven selected MAR interventions in India, Adarsha watershed –Andhra Pradesh, Gokulpura-Goverdhanpura watershed – Rajasthan, Kodangipalayam watershed – TamilNadu, Chikalgaon watershed – Maharashtra, Rajasamadhiyala watershed – Gujarat, Satlasana watershed– Gujarat and Sujalam Sufalam Yojana – Gujarat. Although, the evaluations of these case studies reportedwere not categorized into performance and impact, most of them have addressed both. However, noneof them could explicitly demonstrate that reported impacts were uniquely related to MAR interventions.If impacts are used as a surrogate for performance, it must be shown that impacts are uniquely linked toMAR interventions.